Spark-plasma-sintering (SPS) of nanostructured titanium carbonitride powders - Angerer, P. (2012)
Spark-plasma-sintering (SPS) compaction experiments of nanostructured titanium carbonitride powders have been performed at 1600 °C and 1800 °C (sintering time = 1 min). The as-received nanostructured powders have been synthesized through rapid condensation from the gas-phase (high frequency plasma). The sintering results were compared with data obtained by various conventional sintering techniques such as pressureless sintering, gas pressure sintering, and hot pressing. The phase composition and the crystallite size were investigated by X-ray diffraction (XRD). The fracture surfaces of the sintered samples were inspected with scanning electron microscopy (SEM). The experiments show that the SPS method is capable of obtaining high densities (∼94% of theoretical density) combined with small grain-size quotient d/d0 of 5.4–6.5.